ОПРЕДЕЛЕНИЯ НИОБИЯ И ТАНТАЛА ПИРРОЛИДИНДИТИО КАРБАМИНАТОМ НАТРИЯ В ХЛОРНОКИСЛОЙ СРЕДЕ - Атоев, Э.Х.; Шарипова, Н.У. (SCIENCE and SOCIETY, 2020)
The article describes a method for the determination of niobium with sodium pyrrolidinedithio carbamate (PDTC) in a perchloric acid medium, describes in detail the conditions for determination, the chemistry of the reactions taking place, analyzes the spectra of the products obtained, studies the effect of the solubility of compounds in various solvents, and studies the effect of temperature and solution environment on the course of reactions.